EDUKASI PENGENALAN INVESTASI PADA GENERASI Z SMK MUTIARA BANGSA TIGA - Hendra Wiyanto; Yonathan Reinhard; Ivenny Cecilia; Anthoni Anthoni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Consumerism behavior that has become a habit of society results in a tendency to reduce cultural development. There are still many people who do not realize the importance of having a view of financial management in personal life because of the assumption that personal financial planning in the form of investment is only owned by high-income people. The purpose of carrying out community service for students at SMK Mutiara Bangsa Tiga is to participate in making these students aware through financial counseling, so that generation X and millennials understands and recognize financial literacy and the level of investment that can be made. Exploring investment interests, students’ motivation for personal financial investment planning. And pay attention to the social environment of the students to better understand the investment itself. The implementation method is carried out in four stages including the preparation of materials, making proposals, implementation and reporting processes. The results achieved are that students understand the investment chosen based on personal character in choosing investments that are suitable for moderate, high risk, or low risk.